Separation and isotope ratio measurements of actinides and lanthanides in spent nuclear fuel samples by CE-MC-ICP-MS. Issue 11 (4th October 2022) - Dupuis, Erwan; Isnard, Hélène; Chartier, Frédéric
Abstract : CE was hyphenated to MC-ICP-MS in a glove box to measure isotope ratios of actinides and lanthanides in spent nuclear fuel. Abstract : Capillary electrophoresis (CE) was hyphenated to Multi-Collector Inductively Coupled Plasma Mass Spectrometry (MC-ICP-MS) to perform isotope ratio measurements for actinides (U, Pu, Am, and Cm) and lanthanide fission products (Nd, Sm, Eu, and Gd) in a spent nuclear fuel sample. A capillary electrophoresis-inductively coupled plasma mass spectrometry (CE-ICP-MS) method was developed using either α-HMBA or α-HIBA as electrolytes, demonstrating the ability of alpha-hydroxycarboxylic acids to perform the concurrent separation of actinides and lanthanides in a simulated sample and a spent Mixed Oxide (MOX) fuel sample. Isotope ratios for U, Pu, Am, and Cm as well as Nd, Sm, Eu, and Gd were then determined by CE-MC-ICP-MS in two injections of approximately 30 nL of the spent MOX fuel sample. The relative standard deviations were in the per-mil range, similar to the ones obtained by two-step offline chromatography followed by Thermal Ionisation Mass Spectrometry (TIMS). The use of CE as the separation method lowered the sample quantity (in the pg range for Pu, Am, Cm and lanthanides, in the ng range for U) and waste volume production (a few hundred μL) as compared to commonly used chromatography methods. CE-MC-ICP-MS therefore makes it possible to measure multiple isotope ratios at a per-mil level of uncertainty without the need for prior offline chemical separation.